An investigation into the types of classroom tasks senior secondary school (grade 11 and 12) mathematics teachers give to their learners : a case study - Shapange, Ismael (Rhodes University, Faculty of Education, Department of Education, 2015)
This interpretive case study was undertaken to investigate the nature of classroom tasks that teachers give to their learners and to gain insights into how they choose these tasks. It was carried out at two secondary schools in the Okahao circuit of the Omusati region in Namibia. The schools range from Grade 8 to Grade 12. This study focused mainly on teachers who teach Mathematics at senior secondary phase (Grade 11 and 12). The research participants were of four mathematics teachers "“ two from each school. The study was designed around two phases. Phase one consisted of video-recording of lessons, and phase two consisted of interviewing the teachers. The main purpose of the study was to ascertain the types and nature of tasks that teachers give to their learners and to gain insights into how they chose these tasks. The research adopted a combination of both qualitative and quantitative approaches. The study revealed that the participating teachers provided a near equal amount of lower level cognitive tasks and higher level cognitive tasks. It further revealed several factors that influence teachers when selecting the types of tasks they give to their learners. These factors include curriculum requirements, types of learners and their experiences, and learners' contexts.
Keywords: Mathematics -- Study and teaching (Secondary) -- Namibia -- Omusati; Task analysis in education -- Namibia -- Omusati; Student-centered learning -- Namibia -- Omusati; High school teaching -- Namibia -- Omusati